Formation of highly effective sports teams: an acmeological approach to team building - Bykov, A.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to reveal the regularities of a sports team achieving the state of “acme” – the highest results of activity; to determine the factors of acmeological development and the criteria of team acme, and to substantiate the technologies for forming highly effective sports collectives. Methods and structure of the study. The study has a theoretical-methodological orientation and relies on the acmeological approach. Methods of analysing the scientific literature on psychology, pedagogy, and the theory of sports were used, as well as the generalisation of the practical experience of successful teams. Particular attention is paid to the criteria, conditions, and technologies of achieving team acme. Results and conclusions. It was established that team acme represents an optimal state of the team, characterised by the maximum realisation of potential, synchronicity of actions, creative interaction, and resistance to stress. The key factors of the acmeological orientation of development were identified: high standards, a culture of excellence, innovativeness, systematicity, and personalisation of preparation. The criteria of team acme were substantiated and methods of their diagnosis were proposed. Acmeological technologies of team building were developed: the setting of super-tasks, the creation of a developing environment, a culture of excellence, the individualisation of preparation, and innovative development. A model of the acmeological support of the team is presented, including diagnostic, goal-setting, planning, implementing, controlling, and correcting components. The conditions for achieving acme were determined: qualified leadership, a modern material-technical base, scientific-methodological and psychological support, and a recovery system.